2005
DOI: 10.1073/pnas.0504230102
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of a subregion of human proinsulin by class I-restricted T cells in type 1 diabetic patients

Abstract: Proinsulin is a key autoantigen in type 1 diabetes. Evidence in the mouse has underscored the importance of the insulin B chain region in autoimmunity to pancreatic beta cells. In man, a majority of proteasome cleavage sites are predicted by proteasome cleavage algorithms within this region. To study CD8 ؉ T cell responses to the insulin B chain and adjacent C peptide, we selected 8-to 11-mer peptides according to proteasome cleavage patterns obtained by digestion of two peptides covering proinsulin residues 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
171
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(179 citation statements)
references
References 47 publications
(46 reference statements)
6
171
1
Order By: Relevance
“…Using computer-based binding algorithms, we identified preproIAPP5-13 as an HLA-A*0201 epitope recognized by CTLs in individuals with recent-onset type 1 diabetes (10). In addition, Toma et al (11) recently reported three peptide epitopes located in the proinsulin region that were predicted by proteasomal cleavage databases. In both of the latter studies, peripheral blood mononuclear cells (PBMCs) were tested directly ex vivo for their ability to recognize peptide, using ␥-interferon (IFN-␥) enzymelinked immunospot (ELISpot) assays.…”
Section: Although Both Cd4mentioning
confidence: 99%
“…Using computer-based binding algorithms, we identified preproIAPP5-13 as an HLA-A*0201 epitope recognized by CTLs in individuals with recent-onset type 1 diabetes (10). In addition, Toma et al (11) recently reported three peptide epitopes located in the proinsulin region that were predicted by proteasomal cleavage databases. In both of the latter studies, peripheral blood mononuclear cells (PBMCs) were tested directly ex vivo for their ability to recognize peptide, using ␥-interferon (IFN-␥) enzymelinked immunospot (ELISpot) assays.…”
Section: Although Both Cd4mentioning
confidence: 99%
“…Furthermore, more recent studies in type 1 diabetes (T1D) (Amrani et al, 2000;Toma et al, 2005;Mallone et al, 2007) and multiple sclerosis (Crawford et al, 2004) have highlighted the fundamental contribution of CD8 + T cells in autoimmunity (Liblau et al, 2002;Walter and Santamaria, 2005), thus challenging the paradigm depicting these diseases as predominantly CD4 + T helper 1-mediated.…”
Section: Introductionmentioning
confidence: 99%
“…Their mean age at diagnosis was 27.6 Ϯ 8.4 years, and their median type 1 diabetes duration at the time of the first blood draw was 13 days (2-180). Fifteen age-matched healthy control subjects (mean age 28.8 Ϯ 5.9) were also tested twice within a median follow-up period of 14 months (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Most Cd8mentioning
confidence: 99%